2000
DOI: 10.1046/j.1365-3156.2000.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Are there simple measures to reduce the risk of HIV infection through blood transfusion in a Zambian district hospital?

Abstract: Summary objective  To quantify the potential impact of simple measures to reduce the risk of iatrogenic HIV infection through blood transfusion in a Zambian district hospital. methods  Three studies were conducted at St. Francis' Hospital, Katete, Zambia: (1) From 1991 to 1995 HIV seroprevalence among all listed blood donors and the impact of proper subgroup selection were studied retrospectively; (2) the sensitivity of locally used rapid antibody assays (HIV‐spot/Wellcozyme HIV 1 & 2) for the detection of HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Simple measures such as sub-group selection of donor, stricter indication for blood transfusion and correct use of non-expired tests have been speculated to decrease the risk of iatrogenic HIV transmission. 11 Extending these simple measures to our centre may be difficult for some reasons. Commercial blood donors, the major source of donor blood in our environment, may refuse pre-donation screening.…”
Section: Resultsmentioning
confidence: 99%
“…Simple measures such as sub-group selection of donor, stricter indication for blood transfusion and correct use of non-expired tests have been speculated to decrease the risk of iatrogenic HIV transmission. 11 Extending these simple measures to our centre may be difficult for some reasons. Commercial blood donors, the major source of donor blood in our environment, may refuse pre-donation screening.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of human error to the risk of pathogen transmission is reported to be very low in high-HDI countries [53]. In low-HDI countries, however, what little data there are, indicate that human error can contribute up to 20% of the HIV transmission risk [54,55]. An overview of interventions improving transfusion safety in a selection of African countries revealed that interventions reducing human error in screening and processing of blood donations were cost-effective [49].…”
Section: Discussionmentioning
confidence: 99%
“…Sirs , In the paper by Van Hoogstraten et al . (2000) a serious error occurred in the Methods section, which has direct implications for the conclusions that the authors draw.…”
mentioning
confidence: 99%